Penguatan Hak Ulayat Laut Komunitas Nelayan di Maluku Tengah, Provinsi Maluku - Hijjang, Pawennari (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2012)
This article explained to describe the sea as a customary right of local institutions that by the fishing communities of various ethnic groups for marine resource management in Central Maluku district. Research problems are parsed using procession approach with emphasis on research and research process is not trapped within a rigid framework of theoretical research and is stereotypic. Data collection techniques used were in- depth interviews, participant observation, and focus group discussions (FGD). The process of data analysis includes examining, selection; categorization, evaluation, and synthesis are carried out cyclical and inferences. The results of this study showed that the existence of customary rights as a sea of local institutions that used by the fishermen community, and embodied in the creation of a harmonious society in managing marine resources.